2013
DOI: 10.1371/journal.pone.0061782
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors of Addictive Internet Use among Adolescents in Wuhan, China: Interactions of Parental Relationship with Age and Hyperactivity-Impulsivity

Abstract: PurposesThis study examined the prevalence of addictive Internet use and analyzed the role of parental relationship in affecting this behavior among a random sample of adolescents in Wuhan, China.MethodsStudents (n = 1,101) were randomly selected from four schools, including 638 boys and 463 girls with a mean age of 13.8 (standard deviation = 1.2) years. Addictive Internet use, parental relationship, hyperactivity-impulsivity were measured by validated instruments. Prevalence rate, ANOVA and multiple linear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 50 publications
(41 reference statements)
6
51
0
6
Order By: Relevance
“…Reported rates vary from 2.4% to 13.5% in Chinese schools (Deng et al 2007;Wu et al 2013) and from 1.6% to 20.3% in South Korean adolescents (Kim et al 2006). In the United States, rates vary from 0.7% to 26.3% in adolescents and college students (Moreno et al 2011).…”
Section: Global Prevalence Of Iamentioning
confidence: 99%
“…Reported rates vary from 2.4% to 13.5% in Chinese schools (Deng et al 2007;Wu et al 2013) and from 1.6% to 20.3% in South Korean adolescents (Kim et al 2006). In the United States, rates vary from 0.7% to 26.3% in adolescents and college students (Moreno et al 2011).…”
Section: Global Prevalence Of Iamentioning
confidence: 99%
“…15,16 A study done by Ghamari et al among Iranian medical students, had shown the overall prevalence of internet addiction to be 10.8% with moderate and severe internet addiction equal to 8% and 2.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…20 The data available from the various community and online surveys suggest that internet addiction appears to have a male preponderance, which was observed in our study also. [15][16][17][18][19] This may be due to the gizmo friendly behaviour of males as well as their more interest in games. Among the other sociodemographic variables, Age less than 20 years was one of the other risk factors for internet addiction; younger students were at a significantly higher risk as compared with those over 20 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations can be found in clinical researches in China, which have contributed to the previous literature by focusing on the ways in which Internet adoption shapes subjective well-being among adolescents. Accordingly, problematic and addictive Internet use is associated with increased depression and decreased life satisfaction among Chinese adolescents (Lam and Peng, 2010;Wu et al, 2013). Meanwhile, other studies suggest that appropriate Internet use may improve subjective well-being (Wang and Wang, 2011;Lee et al, 2012;Li, Shi, and Dang, 2014).…”
Section: The Social Implications Of Internet Adoptionmentioning
confidence: 99%